EFFECT OF HUMAN CAPITAL INVESTMENT ON ECONOMIC GROWTH AND PRODUCTIVITY: A SIMULATION APPROACH - Ali Khan, Afaq; Ahmed, Prof. Dr. Roohi (The journal of contemporary issues in business and government, 2022)
The study investigates the dynamiceffects of incomeon a new cohort oflabor force byusing real demography in order to increase investment on human capital. The study constructed three scenarios such as baseline, typical, and optimistic.In the baseline scenarios,the rate of human capital investment,which is observed in 2020 remains constant in 2060,whereas, typical and optimistic scenarios.the rate of human capital increased for each country to median and 75th percentile.The study computes result for each country separately for 40 years into the future, from 2020 to 2060, then average out the findings throughout the complete sample, which the study refers to as the world. Theglobal human capital per worker is computed in absolute terms. In base case scenario, where investment on human capital remain unchanged, the human capital per worker increases in the next four decades, primarily due to demographic changes. Human capital per worker grows somewhere under typical and optimistic scenarios, from around 1.13 to 1.62 and 1.20 to 1.729, respectively. While human capital expands under 50th and 75th percentile from 0.59 to 0.62 and 0.63 to 0.66 respectively.